MECHANICAL PERFORMANCE OF INJECTED STEEL‐REINFORCED RESIN CONNECTORS UNDER DIFFERENT CONFINED CONDITIONS FOR REUSABLE COMPOSITE STRUCTURES. Issue 1 (26th April 2023) - Christoforidou, A.; Kavoura, F.; Pavlovic, M.; Veljkovic, M.
Abstract: A novel injection material for the development of demountable injected bolted connections in oversized holes has been recently developed by the Steel and Composite Structure research group at Delft University of Technology [1]. This injection material is a steel‐reinforced resin (SRR) which consists of spherical steel particles embedded in a resin. The SRR proved to have several benefits such as the increase of the stiffness and strength of the connection and the decrease of its creep deformation when compared to injected connections with conventional epoxy resin. Research on the performance of the injected steel‐reinforced resin (iSRR) has been focused on steel‐to‐steel, steel‐to‐concrete, and steel‐to‐FRP connections. This paper presents an overview of the recent experimental and numerical research on the mechanical properties of demountable iSRR connections and provides a comparison between different confined conditions of the injected volume.